The Criminal Justice for Autism in Indonesia Case Study (Società e diritti, 2020)
Abstract: This study aims to find out how law enforcement for crimes committed by autistic people in Indonesia. This research is a qualitative research with a normative juridical approach. The method used in this research is the study of literature, with descriptive data analysis. The protection of persons with disabilities has been regulated in Indonesian law listed in the Law of the Republic of Indonesia Number 8 of 2016 concerning Persons with Disabilities. The law refers to international conventions (The United Nations Convention on the Rights of Persons with Disabilities). Persons with disabilities as referred to in this law include autism as intellectual disabilities. Although it has been regulated in legislation that persons with autism get the same rights and obligations in law as other citizens, in reality it is not uncommon for cases to end in injustice for them. Some criminal cases involving autistic persons often experience difficulties in their resolution, due to lack of understanding of law enforcement officers. The study states that to provide the fairest possible action for persons with autism, law enforcement must be able to ascertain their physical and psychological condition. This is done through a special approach and assistance from experts and people who are able to create comfort for autistic people is very influential, so that the information received is accurate. An assembly in giving the fairest decision, must be able to consider the opinions of experts, especially those who understand autism.
Keywords: Keywords: Autism, Disabilities, Criminal Justice, Indonesia's Legal